Information technology for management - Turban, Efraim; Pollard, Carol; Wood, Gregory R. (John Wiley & Sons, 2018)
Information technology is ever-changing, and that means that those who are working, or planning to work, in the field of IT management must always be learning. The book also features a blended learning approach that employs content that is presented visually, textually, and interactively to enable students with different learning styles to easily understand and retain information. Coverage of next technologies is up to date, including cutting-edged technologies, and case studies help to reinforce material in a way that few texts can.